Pathological fracture of the jaw due to osteomyelitis after a third molar extraction - Pimentel, Thais; Hadad, Henrique; Jesus, Laís Kawamata; Colombo, Luara Teixiera; Alcantara, Albertino Gomes; Souza, Francisley Ávila; Gárcia-Júnior, Idelmo Rangel (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The osteomyelitis is an inflammatory process in bone tissue caused by an infection, commonly related to anaerobic pathogens, frequently Staphylococcus aureus and Streptococcus sp. Several causes have been related such as dentoalveolar infection, trauma, radiation and genetic condition, but it is not common after surgery for third molar extractions, especially in healthy patients. The symptoms of chronic osteomyelitis usually include signs and symptoms such as pain, edema, suppuration, areas of bone sequestration, and limited mouth opening. Among the complications associated with this condition, pathological fracture may occur due to local bone fragility. This paper aimed to report a rare case of pathological mandible fracture due to osteomyelitis after third molar extraction in a healthy male patient treated by a surgical procedure. The procedure consisted of decortication and resection of the sclerotic bone followed by reduce and fixation of mandibular fracture with one 2.4 reconstructive plate and one 2.0 plate with standard screws.